Efek Media Sosial Konten Keagamaan Terhadap Pemahaman Pelajaran Agama Islam ; Studi Siswa SMKN Gudo Jombang - Qurrotu Aina Al Arafat; Zaimuddin W. As’ad; Moh. Makmun (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to determine the effect of social media use with religious content on students' understanding of Islamic religious studies at Gudo State Vocational School. The method used was quantitative with a correlational approach. The sample in this study consisted of 24 11th-grade students selected using purposive sampling. Data collection used a Likert-scale questionnaire. The analysis results indicate a significant relationshipbetween the use of social media with religious content and students' understanding of Islamic religious studies. This is evidenced by a correlation coefficient of 0.578 with a significance level of 0.003 (<0.05), indicating a moderate and significant correlation. This study concludes that social media has a positive contribution to students' understanding of religion when used appropriately.